Revisiting the effects of unemployment insurance extensions on unemployment: A measurement-error-corrected regression discontinuity approach- - Dieterle, S. Bartalotti, O. and Burmmet, Q. (American Economic Journal Economic Policy)
This study documents two potential biases in recent analyses of UI benefit extensions using boundary-based identification: bias from using county-level aggregates and bias from across-border policy spillovers. To examine the first bias, the analysis uses a regression discontinuity approach that accounts for measurement error in county-level aggregates. These results suggest much smaller effects than previous studies, casting doubt on the applicability of border-based designs. The analysis then shows substantial spillover effects of UI benefit duration on across-border work patterns, consistent with increased tightness in high-benefit states and providing evidence against a dominant vacancy reduction response to UI extensions.- Reproduced